Pembangunan Aplikasi Mobile Game Edukasi Untuk Meningkatkan Kemampuan Mental Math - Daniel Fu; Findra Kartika Sari Dewi; Joseph Eric Samodra (Universitas Atma Jaya Yogyakarta, 2024)
The background for this research is people’s dependence on calculation media such as calculators, even for some of the simplest calculations. Abilities like mental math helps us to reduce dependence on calculators. Which is why a solution is needed to develop mental math ability that is integrated with technology. This research focuses on mobile game development that is based on educational game to develop mental math ability using Android Studio. The game implements the concept of memory game that is integrated with arithmetic rules. It aims for honing critical thinking skills using mental math as well as training memory skills. This game is aimed for people of all ages, but mostly for teenages and youths that are still developing their abilites. Latar belakang penelitian ini adalah ketergantungan orang terhadap media hitung seperti kalkulator, bahkan untuk perhitungan yang paling sederhana sekalipun. Kemampuan seperti matematika mental dapat membantu kita mengurangi ketergantungan terhadap kalkulator. Oleh karena itu dibutuhkan solusi untuk pengembangan kemampuan matematika mental yang terintegrasi dengan teknologi. Penelitian ini berfokus pada pengembangan mobile game berbasis game edukasi untuk pengembangan kemampuan matematika mental menggunakan Android Studio. Game ini mengimplementasikan konsep game memori yang diintegrasikan dengan aturan aritmetika. Tujuannya adalah untuk mengasah kemampuan berpikir kritis menggunakan matematika mental serta melatih kemampuan memori. Game ini ditujukan untuk semua kalangan, namun umumnya untuk remaja dan pemuda yang sedang dalam masa pengembangan kemampuan mereka.